2010
DOI: 10.4310/atmp.2010.v14.n2.a3
|View full text |Cite
|
Sign up to set email alerts
|

$R$-matrices in Rime

Abstract: We replace the ice Ansatz on matrix solutions of the Yang-Baxter equation by a weaker condition which we call rime. Rime solutions include the standard Drinfeld-Jimbo R-matrix. Solutions of the Yang-Baxter equation within the rime Ansatz which are maximally different from the standard one we call strict rime. A strict rime non-unitary solution is parameterized by a projective vector φ. We show that in the finite dimension this solution transforms to the Cremmer-Gervais R-matrix by a change of basis with a matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 18 publications
(37 reference statements)
1
33
0
Order By: Relevance
“…Since the coefficients β and C are arbitrary, the classical Yang-Baxter equation for r splits into three components. The component proportional to β 2 is the classical YangBaxter equation for ρ; it is satisfied: ρ is the classical Cremmer-Gervais r-matrix [9,10]. Next, a straightforward verification shows that …”
Section: Ymentioning
confidence: 91%
See 1 more Smart Citation
“…Since the coefficients β and C are arbitrary, the classical Yang-Baxter equation for r splits into three components. The component proportional to β 2 is the classical YangBaxter equation for ρ; it is satisfied: ρ is the classical Cremmer-Gervais r-matrix [9,10]. Next, a straightforward verification shows that …”
Section: Ymentioning
confidence: 91%
“…Now (9) splits into four components. The component proportional to β 3 vanishes (ρ satisfies a stronger equation, see [10]). Next, a direct verification shows that where p(x, y) is a polynomial of degree not higher than n in x and not higher than n in y.…”
Section: Ymentioning
confidence: 99%
“…In this section, we recall the concept of a weighted infinitesimal unitary bialgebra [19,37], which generalize simultaneously the one introduced by Joni and Rota [29] and the one initiated by Loday and Ronco [35]. Based on the mixture of Eqs.…”
Section: Weighted Infinitesimal Unitary Bialgebras and Examplesmentioning
confidence: 99%
“…In 2010, Ogievetsky and Popov [35] showed that weighted infinitesimal unitary bialgebras play an important role in mathematical physics. Given a solution r ∈ A ⊗ A of the non-homogenous associative classical Yang-Baxter equation, one can construct a weighted infinitesimal unitary bialgebra [35], involving a coproduct given by ∆ r (a) := a · r − r · a − λ(a ⊗ 1) for a ∈ A.…”
Section: Introductionmentioning
confidence: 99%